Reverse Pupillary Block – a Complication of Sutureless Scleral-fixated Intraocular Lenses - Frey, Pirmin; Mueller, Arthur; Markstaller, Monica; Botros, Youssef; Baur, Isabella Diana (Klinische Monatsblätter für Augenheilkunde, 2025)
Reverse pupillary block (RPB) is a posterior bowing of the iris, which is most likely caused by a flap-valve-like mechanism between the lens and the iris. It can lead to iris chafing, pigment dispersion glaucoma and uveitis-glaucoma-hyphema syndrome. In this study we examine patients who underwent sutureless scleral-fixated IOL implantation due to IOL luxation or aphakia. At the follow up visit, a slit-lamp examination, a measurement of the intraocular pressure and an anterior segment OCT (Anterion) were performed. Of 41 eyes, eleven showed the constellation of an RPB. This condition is not necessarily associated with elevated intraocular pressure, but can lead to the above-mentioned complications in the long term. We found that YAG-Laser iridotomy was effective to treat RPB in cases with adequate visualisation of the iris, but surgical idridectomy may be needed in cases with anterior chamber haemorrhage. In our opinion, in patients with a flaccid iris, manifesting as iridodonesis or floppy iris syndrome, as well as in patients who develop RPB postoperatively, either an intraoperative iridectomy or a YAG-laser-iridotomy should be performed.
Keywords: cataract; trauma; glaucoma